Circular RNA Circ_0000098 Elevates ALX4 Expression via Adsorbing miR-1204 to Inhibit the Progression of Hepatocellular Carcinoma - Li, Ming; Yue, Wenjing; Li, Qiankun; Yu, Wenyu; Li, Yao; Cao, Xiaoling (Frontiers in Oncology, 2021)
Background: Circular RNAs (CircRNAs) feature prominently in the progression of various cancers. However, the biological functions of many circRNAs in hepatocellular carcinoma (HCC) are far from fully clarified. This work is performed to decipher the function of circ_0000098 (circSLC30A7) in modulating the progression of HCC and its molecular mechanism. Methods: Microarray data (GSE97332) were available from the Gene Expression Omnibus (GEO) database, and circRNA differentially expressed in HCC tissues was screened out by GEO2R tool. Circ_0000098, microRNA-1204 (miR-1204), and aristaless-like homeobox-4 (ALX4) mRNA expressions were detected by quantitative real-time polymerase chain reaction (qRT-PCR). Cell counting kit-8 (CCK-8), scratch wound healing, and Transwell assays were adopted to determine proliferation, migration, and invasion of HCC cells. ALX4 protein, E-cadherin, N-cadherin, and Vimentin expressions were evaluated by Western blot. In addition, the targeting relationship between miR-1204 and circ_0000098 or ALX4 was studied with dual-luciferase reporter assay and RIP assay. Results: Circ_0000098 expression level was markedly declined in HCC tissues and cells, and its underexpression was associated with larger tumor size of HCC patients. Knocking down circ_0000098 observably promoted the multiplication, migration, invasion, and epithelial-mesenchymal transition (EMT) of Huh7 and SMMC-7721 cells. Additionally, circ_0000098 was mainly distributed in the cytoplasm of HCC cells, and up-regulated ALX4 expression through competitively decoying miR-1204. Conclusion: Circ_0000098, as a competitive endogenous RNA (ceRNA) of miR-1204, upregulates ALX4 expression and suppresses the growth, migration, invasion, and EMT of HCC cells.